SQL Server integration services design patterns - Leonard, Andy; Mitchell, Tim; Masson, Matt; Moss, Jessica; Ufford, Michelle (Apress, 2014)
SQL Server Integration Services Design Patterns is newly-revised for SQL Server 2014, and is a book of recipes for SQL Server Integration Services (SSIS). Design patterns in the book help to solve common problems encountered when developing data integration solutions. The patterns and solution examples in the book increase your efficiency as an SSIS developer, because you do not have to design and code from scratch with each new problem you face. The book's team of expert authors take you through numerous design patterns that you'll soon be using every day, providing the thought process and technical details needed to support their solutions. SQL Server Integration Services Design Patterns goes beyond the surface of the immediate problems to be solved, delving into why particular problems should be solved in certain ways. You'll learn more about SSIS as a result, and you'll learn by practical example. Where appropriate, the book provides examples of alternative patterns and discusses when and where they should be used. Highlights of the book include sections on ETL Instrumentation, SSIS Frameworks, Business Intelligence Markup Language, and Dependency Services. Takes you through solutions to common data integration challenges Provides examples involving Business Intelligence Markup Language Teaches SSIS using practical examples.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed January 8, 2015)
Keywords: SQL server; Database management; Client/server computing; SQL (Computer program language); computerwetenschappen; computer sciences; databasebeheer; database management; Information and Communication Technology (General); Informatie- en communicatietechnologie (algemeen); Bases de données; Gestion; Architecture client-serveur (Informatique); SQL (Langage de programmation); COMPUTERS; Client-Server Computing